Ploidisasi Ikan Mystacoleucus padangensis Bleeker, 1852 (Pisces: Cyprinidae) Melalui Induksi Kejutan Panas (Heat Shock) - Dian Juliadmi; Dewi Imelda Roesma; Djong Hon Tjong (Jurnal Biologi Universitas Andalas, 2015)
Ploidization of Mystacoleucus padangensis Bleeker, 1852 (Pisces: Cyprinid) with heat shock induction has been carried out from January to September 2014 at Genetics and Cytology Laboratory, Biology Department of Faculty of Mathematics and Natural Sciences, Andalas University. This study aimed to find suitable temperature for ploidizatiom on M. padangensis. The study used Completely Randomized Design method with five treatments and five replications. The treatments were various water temperatures (i.e. 27oC as control, 36oC, 38oC, 40oC, and 42oC). The results showed that triploid individuals were found in all treatments but not control. Keywords: ploidization, Mystacoleucus padangensis, heat shock